Medical Dominance in Global Health Institutions as an Obstacle to Equity and Effectiveness; Comment on "Power Dynamics Among Health Professionals in Nigeria: A Case Study of the Global Fund Policy Process" - Sarah L. Dalglish; Olutobi A. Sanuade; Stephanie Topp (Kerman University of Medical Sciences, 2023)
Medical professionals exercised structural and productive power in the Global Fund's Country Coordinating Mechanism (CCM) in Nigeria, directly impacting the selection of approaches to HIV/AIDS care, as described in a case study by Lassa and colleagues. This research contributes to a robust scholarship on how biomedical power inhibits a holistic understanding of health and prevents the adoption of solutions that are socially grounded, multidisciplinary, and co-created with communities. We highlight Lassa and colleagues' findings demonstrating the 'long arm' of global health institutions in country-level health policy choices, and reflect on how medical dominance within global institutions serves as a tool of control in ways that pervert incentives and undermine equity and effectiveness. We call for increased research and advocacy to surface these conduits of power and begin to loosen their hold in the global health policy agenda.